Multifunctional triboelectric nanogenerator for wind energy harvesting and mist catching - Zhang, Fei; Zheng, Lin; Li, Hao; Yu, Gao; Wang, Shengbo; Xing, Fangjing; Wang, Zhong Lin; Chen, Baodong (Chemical engineering journal (Lausanne, Switzerland : 1996), 2024)
In order to comprehensively harness natural resources, a multifunctional triboelectric nanogenerator (MF-TENG) has been developed, capable of simultaneously harvesting wind energy and catching mist. The structure of MF-TENG is simple and cost-effective, facilitating the construction of an in-situ self-powered sensing system, and efficient catching of freshwater from mist. [Display omitted] •A multifunctional triboelectric nanogenerator (MF-TENG) is proposed for harvesting wind energy.•Electrical output performance of MF-TENG was enhanced by designed FEP-2 layer for high-efficiency mist catching.•A self-powered liquid level alarms system was successfully demonstrated. Wind and mist, two ubiquitous phenomena in the natural environment, hold considerable reservoirs of energy. As the focus on renewable energy and freshwater resources intensifies, they have become subjects of extensive research. However, there is a notable scarcity of effective technologies capable of concurrently harnessing both these resources. Here, a multifunctional triboelectric nanogenerator (MF-TENG), employing a rotational structure, has been demonstrated to concurrently harvest wind energy for electricity generation and catch freshwater from mist. Distinguished by an innovative sealing structure, the MF-TENG excels in efficiently catching mist while sustaining a high electrical output, and remarkably resilient to environmental humidity. The MF-TENG achieves an impressive peak open-circuit voltage of 5.44 kV and a peak transferred charge of 328 nC. Furthermore, it demonstrates a maximum mist-catching capacity of 1.867 kg m−2 h−1, coupled with an efficiency of 31.19 %. Notably, the incorporation of FEP-2 results in a remarkable surge of 211 % in open-circuit voltage and an impressive enhancement of 158 % in transferred charge for the MF-TENG at a rotation speed of 200 r/min. The work introduces a pioneering perspective for future sustainable energy and freshwater catching from mist, poised to significantly advance in the comprehensive utilization of natural resources.